HIV-1 uncoating by release of viral cDNA from capsid-like structures in the nucleus of infected cells - Müller, Thorsten G.; Zila, Vojtech; Peters, Kyra; Schifferdecker, Sandra; Stanić, Mia; Lucic, Bojana; Laketa, Vibor; Lusic, Marina; Müller, Barbara; Kräusslich, Hans-Georg (eLife, 2021)
HIV-1 replication commences inside the cone-shaped viral capsid, but timing, localization, and mechanism of uncoating are under debate. We adapted a strategy to visualize individual reverse-transcribed HIV-1 cDNA molecules and their association with viral and cellular proteins using fluorescence and correlative-light-and-electron-microscopy (CLEM). We specifically detected HIV-1 cDNA inside nuclei, but not in the cytoplasm. Nuclear cDNA initially co-localized with a fluorescent integrase fusion (IN-FP) and the viral CA (capsid) protein, but cDNA-punctae separated from IN-FP/CA over time. This phenotype was conserved in primary HIV-1 target cells, with nuclear HIV-1 complexes exhibiting strong CA-signals in all cell types. CLEM revealed cone-shaped HIV-1 capsid-like structures and apparently broken capsid-remnants at the position of IN-FP signals and elongated chromatin-like structures in the position of viral cDNA punctae lacking IN-FP. Our data argue for nuclear uncoating by physical disruption rather than cooperative disassembly of the CA-lattice, followed by physical separation from the pre-integration complex.